Software Change Management: a Quantified Perspective - Dhamija, Ankit; Sikka, Sunil (International Journal of Engineering and Technology, 2018)
A systematic Change Impact Analysis (CIA) is being used for better change management of software. Also, CIA process is evolved continuously to make it more effective. Software metrics play an important role to evaluate CIA process. Two types of metrics are used to evaluate CIA. First types of metrics are the standard metrics used to evaluate the performance of CIA techniques for example Precision, Recall, F-measure etc. These are most commonly used by researchers. Second types of metrics are those which are used to quantify the change impact which is based on the code/design features. This paper is aimed at identification of these second types of metrics available in literature.Â Â